2020
DOI: 10.1038/s41746-020-0226-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating sources of inaccuracy in wearable optical heart rate sensors

Abstract: As wearable technologies are being increasingly used for clinical research and healthcare, it is critical to understand their accuracy and determine how measurement errors may affect research conclusions and impact healthcare decision-making. Accuracy of wearable technologies has been a hotly debated topic in both the research and popular science literature. Currently, wearable technology companies are responsible for assessing and reporting the accuracy of their products, but little information about the eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
368
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 398 publications
(386 citation statements)
references
References 38 publications
11
368
3
4
Order By: Relevance
“…There was also a lack of detail regarding the performance of the devices themselves in terms of seizure detection and estimation of key parameters such as heart rate. In a recent study [45], researchers compared consumer-grade and research-grade heart rate (HR) and heart rate variability (HRV) estimating wearables (including the Empatica E4 and two other HR sensing devices) and observed that "while the research-grade wearables are the only wearables that provide users with raw data that can be used to visualize PPG waveforms and calculate HRV, the HR measurements tended to be less accurate than consumer-grade wearables. This is especially important for researchers and clinicians to be aware of when choosing devices for clinical research and clinical decision support."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also a lack of detail regarding the performance of the devices themselves in terms of seizure detection and estimation of key parameters such as heart rate. In a recent study [45], researchers compared consumer-grade and research-grade heart rate (HR) and heart rate variability (HRV) estimating wearables (including the Empatica E4 and two other HR sensing devices) and observed that "while the research-grade wearables are the only wearables that provide users with raw data that can be used to visualize PPG waveforms and calculate HRV, the HR measurements tended to be less accurate than consumer-grade wearables. This is especially important for researchers and clinicians to be aware of when choosing devices for clinical research and clinical decision support."…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important for researchers and clinicians to be aware of when choosing devices for clinical research and clinical decision support." [45] This very difficult problem of achieving accurate and reliable continuous sensor data in nonsedentary scenarios is highly significant and worthy of more attention if researchers are to develop robust methods and make valid conclusions from acquired data.…”
Section: Discussionmentioning
confidence: 99%
“…In some regions, oxygen saturation probe delivery services are being implemented, which may facilitate this. Heart rate can also be provided by the patient if they use conventional “wearable” technology, although, given the potential inaccuracies with different devices, the results should not be relied on 20. If time allows, inhaler technique can also be checked.…”
Section: What You Should Covermentioning
confidence: 99%
“…72 Other examples of such efforts include smartphone motor-sensing for detection of early signs of Lyme disease 73, 74 and investigation of wearable devices for cardiac monitoring. 73,75,76 Merck & Co., Inc. (Kenilworth, NJ, USA) also conducted a study in collaboration with Koneksa Health that explored use of mobile health approaches to measure changes in heart rate and blood pressure, which found that mobile health approaches were comparable to standard in-clinic measures and Accepted Article sufficiently sensitive to detect treatment differences, demonstrating potential to capture rich hemodynamic data in early clinical trials to aid decision-making. 77 Digital biomarkers may be particularly useful in disease areas that are hindered by a lack of validated biomarkers to objectively measure disease onset and progression, such as neurodegenerative diseases.…”
Section: Accepted Articlementioning
confidence: 99%